The Effect of The Number of Array Elements from Printed Yagi Antenna Against Power Acquisition Efficiency for Implementation RF Harvesting Energy on Frequency 2.4 GHz - Hendro Darmono; Dwiky Fany Irawan; Aad Hariyadi (Jurnal Jaringan Telekomunikasi, 2022)
Most low-power electronics, such as remote sensors and embedded devices, are powered by batteries. Replacement is expensive when there are hundreds of sensors in remote locations. RF Energy Harvesting can be used to provide an alternative energy source for these types of embedded devices. This study is to analyze the effect of the number of elements of the yagi print antenna array on the efficiency of receiving power at a frequency of 2.4 GHz. The making of this harvesting energy system is aimed at making the energy around us maximally utilized and used as alternative energy by the community. The highest output voltage of the rectifier antenna at a distance of 10 cm from the access point is 216 mV for a single element yagi print antenna, 96 mV for a 2 element yagi print antenna, and 168 mV for a 4 element yagi print antenna. with no load, the number of array elements affects the output voltage of the rectifier in addition to the number of stage voltage multipliers.